Biomimetic and biohybrid systems : 8th International Conference, Living Machines 2019, Nara, Japan, July 9–12, 2019, proceedings /: 8th International Conference, Living Machines 2019, Nara, Japan, July 9–12, 2019, proceedings. (2019) - Unknown
No abstract available